Pension and the Family - Mizuki Komura; Hikaru Ogawa (Institute for the Study of Labor (IZA), 2014)
The effects of pension policies on fertility have been examined in the overlapping generations (OLG) model of unitary household in which no heterogeneity exists between the wife and the husband. This paper departs from the OLG model and focuses on the marital bargaining arising from the heterogeneity in a couple in a non-unitary model. Specifically, this paper examines how the pension policy affects the endogenous fertility of a bargaining couple who have different lifespans. The analysis finds out a new channel of pension policy on fertility decisions: an increase in pension size affects fertility not only via the changes in current and future income, but through a change in marital bargaining power. This channel leads a plausible argument that an increase in a pay-as-you-go (PAYG) pension further accelerates a decline in fertility through the empowerment of women.
Keywords: H55; J12; J13; 330; pension; fertility; longevity; marital bargaining